Bidirectional and Opposite Effects of Naïve Mesenchymal Stem Cells on Tumor Growth and Progression - Faramarz Rahmatizadeh; Shiva Gholizadeh-Ghaleh Aziz; Khodadad Khodadadi; Maryam Lale Ataei; Esmaeil Ebrahimie; Jafar Soleimani Rad; Maryam Pashaiasl (Tabriz University of Medical Sciences, 2019)
Cancer has long been considered as a heterogeneous population of uncontrolled proliferation ofdifferent transformed cell types. The recent findings concerning tumorigeneses have highlightedthe fact that tumors can progress through tight relationships among tumor cells, cellular, andnon-cellular components which are present within tumor tissues. In recent years, studies haveshown that mesenchymal stem cells (MSCs) are essential components of non-tumor cells withinthe tumor tissues that can strongly affect tumor development. Several forms of MSCs have beenidentified within tumor stroma. Naïve (innate) mesenchymal stem cells (N-MSCs) derived fromdifferent sources are mostly recruited into the tumor stroma. N-MSCs exert dual and divergenteffects on tumor growth through different conditions and factors such as toll-like receptorpriming (TLR-priming), which is the primary underlying causes of opposite effects. Moreover,MSCs also have the contrary effects by various molecular mechanisms relying on direct cellto-cell connections and indirect communications through the autocrine, paracrine routes, andtumor microenvironment (TME).Overall, cell-based therapies will hold great promise to provide novel anticancer treatments.However, the application of intact MSCs in cancer treatment can theoretically cause adverseclinical outcomes. It is essential that to extensively analysis the effective factors and conditionsin which underlying mechanisms are adopted by MSCs when encounter with cancer.The aim is to review the cellular and molecular mechanisms underlying the dual effects ofMSCs followed by the importance of polarization of MSCs through priming of TLRs.